Izdelava sestojne karta na podlagi lidarskih podatkov - Bončina, Andrej (Gozdarski vestnik, 2024)
A stand map is a crucial data source for forest stands, and the procedures for its creation can vary. In this paper, we present i) the process of creating an automated stand map (TBk), developed at the Bern University of Applied Sciences (BFH_HAFL), ii) the produced stand maps TBk for the forest areas of Draga and Pokljuka, iii) the classification of stands into stand types in these areas, and iv) the results of comparing the automatic stand map with the stand map produced by the Slovenian Forest Service. In the creation of TBk, the dominant height of vegetation is the fundamental criterion for delineating stands, while dominant height and cover levels in stand layers are fundamental criteria for classifying stands into stand types. The average stand size on the TBk map in Draga and Pokljuka is 1.76 ha and 1.64 ha, which is considerably smaller than the average stand size on the map by the Slovenian Forest Service (5.90 ha and 2.85 ha). In the size structure of stands on the TBk, stands with an area smaller than 0.5 ha predominate. The proportions of stand types on the TBk and map by the Slovenian Forest Service match, but the spatial matching of delineated stands is poorer due to different criteria for delineation and more precise spatial scale applied in the TBk procedure. The relevance of the map is conditioned by the period when the survey was conducted. The advantages of TBk include fast production, objectivity in delineation, the possibility of monitoring changes in forest stands over time, and multi-layered information about stands, with the main limitation being a limited set of stand characteristics (e.g. damage, stand quality) which are register in the terrestrial inventory. In comparison to the common stand map, TBk does not include qualitative stand parameters and planned management activities for the next planning period.
Keywords: classification of forest stands; klasifikacija sestojev; lidar data; lidarski podatki; sestojna karta; stand map; TBk